The Effect of Electroacupunture on the Percentage of Lymphocyte Count on the Peripheral Blood Smear of C3H Mice Breast Adenocarcinoma Model - Kamalia, Rizki; Mihardja, Hasan; Srilestari, Adiningsih; Barasila, Atikah C; Thamrin Akib, Husniah Rubiana (Indonesian Journal of Cancer, 2018)
Background: Breast cancer patients often experience decreased the immune system such as a decreased of lymphocytes, which can increase mortality. Acupuncture is expected to be a therapeutic option to increase lymphocyte because current pharmacological therapy is very expensive with the risk of adverse event. This study aims to prove the action of Electroacupuncture (EA) as an immunomodulator for cellular immunity by increasing the percentage of lymphocytes of Peripheral Blood Smear (PBS) in C3H mice of breast adenocarcinoma model. Methods:Laboratory experimental study with post test only controls group design involving twenty PBS preparations taken from 20 C3H mice of breast adenocarcinoma models divided into 4 groups. Group K with no EA treatment, group P1 was given 1 time EA treatment, group P2 was given 2 times EA treatment and P3 was given 3 times EA treatments (with seven days interval). EA stimulation was performed at ST36 Zusanli, BL18 Ganshu, BL20 Pishu with frequency of 2 Hz for 15 minutes. Result:The mean weight of mice was 23.90 ± 3.03 gr in control group, 25.40 ± 1.54 gr in P1 group, 27.00 ± 3.87 gr in P2 group and 25.90 ± 5.83 gr in P3 group, with most of them were female mice. The mean volume tumor in mice of control group was 14.49 ± 2.75 mm3, 16.72 ± 6,40 mm3 in P1 group, 20.18 ± 5.94 mm3 in P2 group and 22.07 ± 6.51 mm3 in P3 group. The mean percentage of lymphocyte was 44.20 ± 15.72 in control group, 43.00 ± 11.70 in P1 group, 49.60 ± 7.02 in P2 group and 43.20 ± 13.10 in P3 group. The correlation between the number of electroacupuncture treatments on the number of lymphocytes in the treatment group were compared to the control group with p = 0.811. Conclusions: Research acupuncture on cancer management has been done and provided good result. Acupuncture in particular EA has benefits in improving immunity by affecting lymphocyte enhancement. Acupuncture can be considered as adjuvant therapy in cancer patients breast. ABSTRAKLatar Belakang: Pada pasien kanker payudara sering terjadi penurunan sistemimun antara lain menurunnya limfosit, yang dapatm eningkatkan angka kematian. Akupunktur diharapkan dapat menjadi pilihan terapi untuk meningkatkan limfosit karena terapi farmakologi saat ini harganya sangat mahal dengan resiko efek samping. Penelitian ini bertujuan untuk membuktikan bahwa tindakan elektroakupunktur (EA) dapat berefek sebagaii mmunomodulator terhadap imunitas seluler dengan meningkatkan persentase limfosit sediaan apus darah tepi (SADT) pada mencit C3H model adenokarsinoma payudara. Metode: Penelitian eksperimental ini dilakukan dengan post test only control group design terhadap dua puluh sediaan apus darah tepi yang diambil dari 20 mencit C3H model adenokarsinoma payudara. Kelompok studi dibagi menjadi 4 kelompok yaitu Kelompok K tidak diberi perlakuan EA, kelompok P1 dilakukan EA 1 kali, kelompok P2 dilakukan EA 2 kali dan P3 dilakukan EA 3 kali. Tindakan EA dilakukan pada titik ST36 Zusanli, BL18 Ganshu, BL20 Pishu dengan frekuensi 2 Hz selama 15 menit. The